2009
DOI: 10.1002/jmv.21477
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a sensitive and specific real‐time PCR for detection and quantitation of hepatitis B virus covalently closed circular DNA in plasma of chronic hepatitis B patients

Abstract: Hepatitis B virus (HBV) covalently closed circular DNA (cccDNA) serves as a template for viral replication and plays a role in persistence of HBV infection. The origin and significance of cccDNA in plasma however, is not well understood. A sensitive, specific, and reproducible real-time PCR for detection and quantitation of cccDNA in plasma of chronic hepatitis B patients was developed and validated. Four HBV DNA reference panels, and 96 plasma samples of chronic hepatitis B patients were analyzed. Results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The mark of productive virion infection and genome replication, HBV covalently closed circular DNA (cccDNA), was detected using selective PCR technology [11] . Experimental processes and amplified conditions were performed in accordance with references [12,13] . About 10 μg cell DNA was digested with 1 μL Mung bean nuclease (MBN; New England Biolabs, England) enzyme.…”
Section: Detection Of Hbv In Cellsmentioning
confidence: 99%
“…The mark of productive virion infection and genome replication, HBV covalently closed circular DNA (cccDNA), was detected using selective PCR technology [11] . Experimental processes and amplified conditions were performed in accordance with references [12,13] . About 10 μg cell DNA was digested with 1 μL Mung bean nuclease (MBN; New England Biolabs, England) enzyme.…”
Section: Detection Of Hbv In Cellsmentioning
confidence: 99%
“…A major mechanism of HBV persistence during antiviral treatment with Nuc is persistence of cccDNA in infected cells. 11,12 A reduced cell death rate of infected cells could explain why HBV persists during effective antiviral treatment. 13 HBs-Antigen decline during antiviral treatment indicates reduction of HBV infected cells.…”
Section: Introductionmentioning
confidence: 98%
“…Some reports have shown that cccDNA is present in patients’ sera and that it is a marker of off-treatment virological relapse [11,26,32,34,114], whereas others have refuted the existence of cccDNA in serum and have used DNA extracted from CHB patients’ sera as a negative control in the quantification of intracellular cccDNA [39,42,63]. Do some non-liver cells, such as PBMCs, support HBV infection and formation of cccDNA?…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…To further increase the sensitiveness and accuracy, Singh et al applied two hybridization fluorescence resonance energy transfer (FRET) probes in LightCycler TM (Roche Diagnostic, Mannheim, Germany) real-time PCR [41] which were able to maintain a cccDNA:rcDNA specificity ratio greater than 1:10,000. Due to the inherent speed, simplicity and sensitivity of qPCR, subsequent efforts to optimize general real-time PCR conditions [11,12,13,26,32,33,34,38,54,63,69,85,86,87,88,89] (including primers, probe design and sample handling) to effectively distinguish cccDNA from other HBV DNA forms have been made without sacrificing the high amplification efficiency and sensitivity of the method.…”
Section: Cccdna Detection and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation